Critical Evidence - Hakuta, Kenji; Bialystok, Ellen; Wiley, Edward (Psychological Science, 2003)
The critical-period hypothesis for second-language acquisition was tested on data from the 1990 U.S. Census using responses from 2.3 million immigrants with Spanish or Chinese language backgrounds. The analyses tested a key prediction of the hypothesis, namely, that the line regressing second-language attainment on age of immigration would be markedly different on either side of the critical-age point. Predictions tested were that there would be a difference in slope, a difference in the mean while controlling for slope, or both. The results showed large linear effects for level of education and for age of immigration, but a negligible amount of additional variance was accounted for when the parameters for difference in slope and difference in means were estimated. Thus, the patterh of decline in second-language acquisition failed to produce the discontinuity that is an essential hallmark of a critical period.